EFFECT OF FLOWER WRITING STRATEGY ON WRITING SKILLS OF FABLE STORY TEXT IN STUDENTS OF CLASS VIII MTs - Iseu Lilis Hendrayani (JLER (Journal of Language Education Research), 2022)
This study aims to describe the effect of using the flower writing strategy on the writing skills of the eighth grade students of MTS Persis 50 Lembang. The data of this research is in the form of a score of writing skills for fable stories without and using mind mapping techniques. This type of research is quantitative research conducted using an experimental design. The results of this study are that the skills of writing fable texts for class VIII MTS Persis 50 Lembang students do not use mind mapping techniques but still have more than adequate qualifications and the skills of writing fable texts for class VIII MTS Persis 50 Lembang students using flower writing strategies are good qualifications. Based on the t-test, it was concluded that the use of flower writing strategy had an effect on the writing skill of the fable text.